Comparison Of Oral And Intravenous Iron Therapy In Geophagic Botshabelo Women With Iron Deficiency Anaemia - Mogongoa, Lebogang Francis (Central University of Technology, 2020)
Geophagia, the habitual consumption of soil, is associated with iron deficiency anaemia (IDA), especially in women of childbearing age. Geophagia and IDA are very prevalent in southern Africa. The reasons for the association of geophagia with IDA are numerous but the one that has prominence is mineral supplementation. However, there is contradictory in vitro evidence; with studies that support supplementation versus studies that postulate removal of iron. If soil reduces the bioavailability of dietary iron, could it also interfere with the treatment of IDA? The current treatment protocol of IDA is with oral iron and if oral iron is not effective then intravenous iron therapy is undertaken. The challenge would be that the patient would suffer symptoms of anaemia while on oral iron therapy. This study aimed to determine if oral or intravenous iron therapy will be effective for the treatment of IDA in non-pregnant geophagic Botshabelo females. A study comparing oral and IV iron therapy has not been performed before. In this randomised prospective doseescalating intervention study a group of geophagic females with IDA were recruited and randomly assigned to two groups. Group A was expected to abstain from soil consumption and group B continued with soil consumption. Both groups received oral iron therapy for ten weeks. During this period, study-related procedures and blood analysis and questionnaires, at different time intervals to assess the effects of oral therapy, were undertaken. At the end of ten weeks, IV iron therapy was administered to those participants who did not respond to oral therapy. Of the 320 recruited participants only 83 met the inclusion criteria. At baseline, the general health indicators pointed towards an otherwise healthy population group with hypertension, obesity and IDA as exceptions. Randomisation into two groups was effective as there was no significant difference between the two groups at baseline. There were no other confounding factors that could have resulted in the changes observed in the study population. The absence of these confounding factors was due to non-aberrant findings in blood loss or nutrition; absence of other medication or diseases that could interfere with oral therapy; normal liver enzyme levels, minerals and normal general health indicators. There were no significant red blood cell parameter changes for both short (week 4) and intermediate (week 7) follow up periods of oral therapy for both groups. Group A showed a statistical but clinically insignificant increase for the red blood cell parameters contrary to group B which did not show changes. While serum iron, total iron-binding capacity and transferrin saturation showed statistical but clinical insignificant changes for both groups. The expected endpoint was not achieved for both groups, signifying that oral iron was not effective in the treatment of IDA in geophagia. Soil decreased oral iron therapy bioavailability because group B did not show significant changes. The clinical insignificant increase in group A also implied that the absorptive surface of the gastrointestinal tract was affected and did not recover within the ten weeks. For IV iron therapy, both groups showed a statistical and clinically significant increase for red blood cell and iron study parameters for both short and long term follow up study periods. Moreover, the changes for red blood cell and iron study parameters achieved the desired endpoint for therapy. Therefore, IV iron therapy was effective while oral iron therapy was not. These findings are contrary to other study fields’ observation where both oral and IV iron were both effective. It can be concluded that oral iron therapy is not effective for the treatment of IDA in geophagia while IV iron is effective. Oral iron’s non-effectiveness indicates that the patient will bear the symptoms of IDA while therapy is not effective. This study supports the use of IV iron for the treatment of IDA in geophagia, thus necessitating the change of iron therapy protocol for the benefit of geophagic IDA patients.
Thesis